Wspomagane samobójstwo w świetle orzecznictwa Europejskiego Trybunału Praw Człowieka - Łukasik, Magdalena (Progress. Journal of young researchers, 2024)
Modern society is a society accustomed to a life of prosperity and develop-ment. This causes people, at the very thought of constant pain (both mentaland physical), to look for a solution that can shorten it. This state of affairs is in-fluenced by utilitarianism (which proclaims that there is no point in suffering)which is popular in highly developed societies. According to the Convention for the Protection of Human Rights and Funda-mental Freedoms, every human being is free and therefore decides for him-self/herself about his/her own life (including how to end it), but accordingto the same document, life is a legal good protected by law. Proponents of eu-thanasia and assisted suicide emphasise that a sick person can die with dig-nity thanks to a euthanasia procedure. They emphasise that human dignityis an overriding value protected by law. Opponents of euthanasia, on the oth-er hand, argue that human life should not be valued. No one can decide whichlife can continue and which should be terminated.The institution that tries to settle the dispute between supporters and op-ponents of euthanasia is the European Court of Human Rights. Accordingto the Court, the freedom to allow legal euthanasia must have a limit. This limitis Article 2 of the Convention and the control exercised by the ECtHR. Each per-son’s case is different and subject to individual examination.